Discove Cottage in Bruton, Somerset, England - Unknown:::Creator:::::::::::: (England, 2022)
Front view of Discove Cottage John and Elaine stayed here for most of 1959 when Steinbeck was researching and writing The Acts of King Arthur and his Noble Knights. Bruton, a place of considerable antiquity, is a small town in Somersetshire on the river Brue, about 117 miles from London. Original in safe.